Analyzing the cognitive academic mathematical communication in an online distance learning for grade 11 - Italia, Mary Joyce N. (Animo Repository, 2023)
A multi-phase mixed-method study, particularly a combination of convergent parallel and explanatory sequential research design, was conducted to analyze the cognitive academic mathematical communication of Grade 11 in an online distance learning context. Instruments such as synchronous and asynchronous observation checklists, a survey questionnaire, and Cognitive Academic Language Questionnaire – Patterns and Algebra (CALQ-PA) were utilized to determine how students manifested their understanding using the academic language of mathematics. Likewise, the strategies employed by teachers were also examined. From a total population of 1099 students, 374 participated in answering the survey questionnaire, while 174 in the CALQ-PA. The results revealed that most online distance learners have below-basic vocabulary and syntactic knowledge. Subsequently, the problem-solving section shows that the participants are advanced in the reading stage, proficient in comprehension, transformation, and process-skill, and have basic skills in the encoding stages. Further elaborations and educational implications were also discussed. Keywords: Mathematical Communication, CALP, Mathematical Vocabulary Knowledge, Mathematical Syntactic Knowledge, Problem Solving